Pathophysiology of Skin Resident Memory T Cells - Tokura, Yoshiki; Phadungsaksawasdi, Pawit; Kurihara, Kazuo; Fujiyama, Toshiharu; Honda, Tetsuya (Frontiers in Immunology, 2021)
Tissue resident memory T (TRM) cells reside in peripheral, non-lymphoid tissues such as the skin, where they act as alarm-sensor cells or cytotoxic cells. Physiologically, skin TRM cells persist for a long term and can be reactivated upon reinfection with the same antigen, thus serving as peripheral sentinels in the immune surveillance network. CD8+CD69+CD103+ TRM cells are the well-characterized subtype that develops in the epidermis. The local mediators such as interleukin (IL)-15 and transforming growth factor (TGF)-β are required for the formation of long-lived TRM cell population in skin. Skin TRM cells engage virus-infected cells, proliferate in situ in response to local antigens and do not migrate out of the epidermis. Secondary TRM cell populations are derived from pre-existing TRM cells and newly recruited TRM precursors from the circulation. In addition to microbial pathogens, topical application of chemical allergen to skin causes delayed-type hypersensitivity and amplifies the number of antigen-specific CD8+ TRM cells at challenged site. Skin TRM cells are also involved in the pathological conditions, including vitiligo, psoriasis, fixed drug eruption and cutaneous T-cell lymphoma (CTCL). The functions of these TRM cells seem to be different, depending on each pathology. Psoriasis plaques are seen in a recurrent manner especially at the originally affected sites. Upon stimulation of the skin of psoriasis patients, the CD8+CD103+CD49a- TRM cells in the epidermis seem to be reactivated and initiate IL-17A production. Meanwhile, autoreactive CD8+CD103+CD49a+ TRM cells secreting interferon-γ are present in lesional vitiligo skin. Fixed drug eruption is another disease where skin TRM cells evoke its characteristic clinical appearance upon administration of a causative drug. Intraepidermal CD8+ TRM cells with an effector-memory phenotype resident in the skin lesions of fixed drug eruption play a major contributing role in the development of localized tissue damage. CTCL develops primarily in the skin by a clonal expansion of a transformed TRM cells. CD8+ CTCL with the pagetoid epidermotropic histology is considered to originate from epidermal CD8+ TRM cells. This review will discuss the current understanding of skin TRM biology and their contribution to skin homeostasis and diseases.